2019
DOI: 10.1038/s41419-019-1776-x
|View full text |Cite
|
Sign up to set email alerts
|

GLI1 activation by non-classical pathway integrin αvβ3/ERK1/2 maintains stem cell-like phenotype of multicellular aggregates in gastric cancer peritoneal metastasis

Abstract: Peritoneal metastasis is one of the most important causes of postoperative death in patients with gastric cancer, and the exact mechanism remains unclear. The proliferation of multicellular aggregates of exfoliated malignant gastric cells in the abdominal cavity is the focus of current research. However, the mechanism how gastric cancer multicellular aggregates survive remains unclear. In this study, we demonstrated that multicellular aggregates of exfoliated gastric cancer cells in the abdominal cavity expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…In previous researches, a large number of studies have elucidated the MAPK signaling, focal adhesion pathway, cGMP-PKG signaling pathway and etc. were closely or partially related to peritoneal metastasis of GC (63)(64)(65)(66)(67). Similar to the findings, the present study observed that 214 genes positively associated with PRIs enriched mainly in MAPK and focal adhesion pathway (Figure 5A), suggesting the major role of these two pathways taking on the peritoneal relapse of GC.…”
Section: Discussionsupporting
confidence: 89%
“…In previous researches, a large number of studies have elucidated the MAPK signaling, focal adhesion pathway, cGMP-PKG signaling pathway and etc. were closely or partially related to peritoneal metastasis of GC (63)(64)(65)(66)(67). Similar to the findings, the present study observed that 214 genes positively associated with PRIs enriched mainly in MAPK and focal adhesion pathway (Figure 5A), suggesting the major role of these two pathways taking on the peritoneal relapse of GC.…”
Section: Discussionsupporting
confidence: 89%
“…In GC, its expression is significantly higher in metastatic cancer tissues and is positively correlated with a more aggressive tumor phenotype . Furthermore, it has been observed that GLI1 overexpression promotes a CSC phenotype enhancing cell proliferation, migration and therapy resistance (Dong et al, 2019;Yao et al, 2019). GLI1 also plays an important role in CSC characteristics related with aggressiveness and metastatic spread of CRC cells leading to decreased survival.…”
Section: Gli1 (Gli Family Zinc Finger 1)mentioning
confidence: 99%
“…Developing Gli-targeted approach has its merit because of the fact that Gli proteins can be activated by both SHh liganddependent and -independent mechanisms. Gli1 and Gli2 inhibitor include GANT 61 [30] and Arsenic Trioxide [31] that have shown potent inhibition of Gli1 and Gli2 in many cancer cell lines, one of these is GC cells. Currently, many preclinical studies and clinical trials are being conducted to evaluate the efficacy of this exciting class of targeted therapy in a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%